Adolescent Intermittent Ethanol Increases the Sensitivity to the Reinforcing Properties of Ethanol and the Expression of Select Cholinergic and Dopaminergic Genes within the Posterior Ventral Tegmental Area. (21st August 2019) - Hauser, Sheketha R.; Knight, Christopher P.; Truitt, William A.; Waeiss, Robert Aaron; Holt, Ian S.; Carvajal, Gustavo B.; Bell, Richard L.; Rodd, Zachary A.
Abstract : Background: Although not legally allowed to consume alcohol, adolescents account for 11% of all alcohol use in the United States and approximately 90% of adolescent intake is in the form of an alcohol binge. The adolescent intermittent ethanol (AIE) model developed by the NADIA consortium produces binge‐like EtOH exposure episodes. The current experiment examined the effects of AIE on the reinforcing properties of EtOH and genetic expression of cholinergic and dopaminergic factors within the posterior ventral tegmental area (pVTA) in Wistar male and female rats and in male alcohol‐preferring (P) rats. Methods: Rats were exposed to the AIE or water during adolescence, and all testing occurred during adulthood. Wistar control and AIE rats were randomly assigned to groups that self‐administered 0 to 200 mg% EtOH. Male P rats self‐administered 0 to 100 mg%. Results: The data indicated that exposure to AIE in both Wistar male and female rats (and male P rats) resulted in a significant leftward shift in dose–response curve for EtOH self‐administration into the pVTA. TaqMan array indicated that AIE exposure had divergent effects on the expression of nicotinic receptors (increased a7, reduction in a4 and a5). There were also sex‐specific effects of AIE on gene expression; male only reduction in D3 receptors. Conclusion: Binge‐like EtOH exposure during adolescence enhances the sensitivity to the reinforcing properties of EtOH during adulthood which could be part of biological sequelae that are the basis for the deleterious effects of adolescent alcohol consumption on the rate of alcoholism during adulthood.